A physiological chamber experiment to explore human thermal adaption on the seasonal scale. Issue 4 (September 2019) - Ji, Wenjie; Cao, Bin; Zhu, Yingxin
Abstract: In the theory of thermal adaption, it's usually believed that people can adapt to the thermal environment actively from three aspects: physiology, psychology and behaviour. The purpose of this study is to explore whether there is some thermal physiological adaption on the seasonal scale. A chamber experiment was designed and conducted twice at spring and early summer with the time interval of 1 month. There were totally four experimental conditions in each experiment, including 16 °C, 22 °C, 28 °C and 34 °C. We measured four physiological parameters of 18 recruited subjects, including in skin temperature, blood flow, moisture evaporation amount and metabolic rate. At the same time, some of the subjective thermal evaluation was collected. It was a tracing experiment in which the same individual was asked to participate in the experiment twice. So, some comparison on physiological parameters and thermal comfort evaluations at different season could be explored to illustrate the characteristics of thermal adaption. We found that there was some obvious difference on the moisture evaporation and the blood flow after one-month adaption, and the thermal comfort vote in the same temperature also had some variation. This study is meaningful for further understanding the mechanism of thermal adaption.